Strategies of Radioiodine Ablation in Patients with Low-Risk Thyroid Cancer - Schlumberger, Martin; Catargi, Bogdan; Borget, Isabelle; Deandreis, Désirée; Zerdoud, Slimane; Bridji, Boumédiène; Bardet, Stéphane; Leenhardt, Laurence; Bastie, Delphine; Schvartz, Claire; Vera, Pierre; Morel, Olivier; et al. (The New England journal of medicine, 2012)
This trial compared two thyrotropin-stimulation methods and two 131I doses for postoperative ablation in patients with low-risk thyroid cancer. Rates of ablation were similar in all treatment groups. Doses lower than those currently recommended may be adequate for this condition. Radioiodine ( 131 i) is administered to patients with thyroid cancer after total thyroidectomy for three reasons 1 – 3 : first, to eradicate normal-thyroid remnants (ablation) in order to achieve an undetectable serum thyroglobulin level; second, to irradiate any neoplastic focus in order to decrease the risk of recurrence; and third, to perform 131 I total-body scanning for persistent carcinoma. Successful ablation is defined by the combination of undetectable serum thyroglobulin levels after thyrotropin stimulation and normal results on neck ultrasonography 6 to 12 months after 131 I administration. 2 , 3 When these criteria are met, approximately 1% of patients have a recurrence. 4 – 6 In . . .